Evaluation of pesticide residues in selected vegetables from Kuala Lumpur, Malaysia using modified QuEChERS and assessment of washing methods - Ishak, Azuha; Pak Dek, Mohd Sabri; Rukayadi, Yaya; Ramli, Nurul Shazini; Wasoh, H. (Universiti Putra Malaysia, 2023)
Growing population in Malaysia has resulted in increased production of local vegetables as well as pesticide usage. This constitutes a health risk to human health. In the present work, the level of ten pesticide residues namely chlorpyrifos, profenofos, aldrin, endrin, cypermethrin, lambda-cyhalothrin, carbendazim, propamocarb, imidacloprid, and thiamethoxam in ten types of vegetables collected from six local markets were measured using modified QuEChERS (quick, easy, cheap, effective, rugged, and safe) coupled with gas chromatography-tandem mass spectrometry (GC-MS/MS) and ultra-performance liquid chromatography-tandem mass spectrometry (UPLC-MS/MS). Results showed that 13.3% samples contained pesticide residues above the maximum residue limit (MRL) prescribed by the Malaysian Food Regulations 1985, 55.0% of samples contained pesticide residues below the MRL, and no pesticide residues were detected in 31.7% of samples. Carbendazim and chlorpyrifos were among the highest pesticides detected in the samples. For the type of vegetables, kale and spinach contained high concentrations of pesticide residues above the MRL. In order to produce safe vegetables, the efficiency of different washing methods (tap water, 10% sodium bicarbonate solution, and 10% acetic acid solution) in reducing carbendazim and chlorpyrifos residues in a kale model system was evaluated. Results showed that the levels of carbendazim and chlorpyrifos reduction for all three methods were significantly different (p < 0.05) with 10% acetic acid solution being the most effective followed by 10% sodium bicarbonate solution, and tap water. Washing kale with 10% acetic acid reduced 76.0 and 41.2% of carbendazim and chlorpyrifos, respectively. Therefore, it is recommended for consumers to practice 10% sodium bicarbonate washing method by soaking vegetables with an acidic solution followed by rinsing with tap water to reduce pesticide residues, and minimise the exposure to hazardous pesticides.